Reproductive factors and thyroid cancer risk: Meta‐analysis. Issue 12 (8th October 2019) - Mannathazhathu, Arathy S.; George, Preethi S.; Sudhakaran, Sreekala; Vasudevan, Durga; Krishna KM, Jagathnath; Booth, Christopher; Mathew, Aleyamma
Abstract: Background: Assessed pooled risk on reproductive factors and oral contraceptives (OC) on thyroid cancer (TC) using published studies (1996‐2017). Methods: Summary odds ratio (OR) for case‐control studies (n = 10) and risk ratio (RR) for cohort studies (n = 9) was done. Results: OR was 1.43 (95% CI: 1.16‐1.77) for age at menarche >14 years, 1.49 (95% CI: 1.19‐1.86) for parity >2, 1.38 (95% CI: 1.18‐1.61) for miscarriage/abortion, and 2.05 (95% CI: 1.39‐3.01) for artificial menopause. A protective effect (ORs: 0.85; 95% CI: 0.72‐0.99) on TC was observed for prolonged use of OCs. RR was 1.17 (95% CI: 0.90‐1.57) for age at menarche >14 years, 1.10 (95% CI: 0.94‐1.27) for parity >2, 1.20 (95% CI: 1.03‐1.40) for miscarriage/abortion, and 2.16 (95% CI: 1.41‐3.31) for artificial menopause and protective effect (RR: 0.78; 95% CI: 0.65‐0.92) for prolonged use of OCs. Conclusions: This meta‐analysis supports an association due to changes in female hormones during menstrual cycle and pregnancy with the risk of TC and explains female preponderance.